Agency and fidelity in primary teachers' efforts to develop mathematical resilience. Issue 1 (1st January 2022) - Lee, Clare; Ward-Penny, Robert
ABSTRACT: Teaching using the principles of mathematical resilience can lead to a broad range of implementations with different emphases, all intended to mitigate the development of mathematical anxiety in learners and its attendant problems. This article considers 12 primary teachers' responses to the challenge of developing mathematical resilience within their practice. In pairs, these teachers conducted a small-scale study in their classrooms on a chosen aspect of mathematical resilience, supported by termly meetings. The reports made by the participant teachers form the main part of the data. The teachers were inspired to change how they worked with their learners and reported many positive outcomes. The agency which some teachers exercised influenced not only their outworking of the ideas, but also the fidelity with which they adopted the principles underpinning mathematical resilience. The connections and tensions shown here between agency and fidelity have wider implications for successful implementation of similar change efforts.